An Analysis of Rapid Reading Skills among Non-Indonesian Language Students at the Faculty of Sports Science and Community Health, Mandalika University of Education - Supriadin, Supriadin; Salabi, Muhamad (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the rapid reading skills of non-Indonesian language majors and the factors influencing them. Employing a quantitative descriptive approach, this research sampled 35 students. Data collection techniques included observation, testing, and documentation. Participants read a 500-word passage, and their reading speed was recorded and timed using a stopwatch. Data analysis utilized the KEM formula. Results showed varied reading skills among students: 15 (42.9%) demonstrated fast reading (337.07 words per minute), 12 (34.3%) moderate (122.44 wpm), and 8 (22.9%) slow (107.52 wpm). Internal and external factors significantly influenced reading speed.